Artificial intelligence and academic writing in the digital age among university students: Why media literacy matters - Elizabeth Ifeoma Anierobi; Amjad Islam Amjad; Sarfraz Aslam; Huda Alshamsi; Abdulnaser Fakhrou; Muhammad Usman Rafique (Environment and Social Psychology, 2026)
The study explored the intersection of artificial intelligence (AI) and academic writing in the digital age among university students, highlighting why media literacy is crucial. The study adopted the descriptive research design and was guided by four research questions. A sample of 310 respondents was selected using a random sampling technique. The data were collected using a questionnaire, the Artificial Intelligence and Academic Writing Questionnaire (AIAWQ). The analysis showed that the utilization of AI for academic writing is prevalent among university students. It was also found that utilizing AI for academic purposes among the students for academic writing has many benefits such as improving quality of students’ assignments, creating in them a sense of confidence in writing their assignments/term papers, helping them to beat deadlines in completing and submitting their assignments, improving their academic performance as a result of quality academic writing and helping students to engage more in their studies at their own pace. The study further found that utilizing AI for academic writing poses no challenges for students. Moreover, the study demonstrated that media literacy plays a crucial role in mitigating the challenges posed by AI usage in academic writing. It was recommended, among others, that media literacy on AI ethics should be included in the school curriculum.